2008
DOI: 10.1677/erc-08-0078
|View full text |Cite
|
Sign up to set email alerts
|

Low phosphorylation of estrogen receptor   (ER ) serine 118 and high phosphorylation of ER  serine 167 improve survival in ER-positive breast cancer

Abstract: Endocrine therapy has become the most important treatment option for women with estrogen receptor (ER)-positive breast cancer. Urgently needed are prognostic assays that can identify those who need additional adjuvant therapy, such as signal transduction inhibitors or chemotherapy, for ER-positive early breast cancer. We examined phosphorylation of ERa serine (Ser) 118, ERa Ser167, p44/42 mitogen-activated protein kinase (MAPK), and Akt and expression of progesterone receptor, amplified in breast cancer 1 (AIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 24 publications
8
86
2
1
Order By: Relevance
“…In particular, phosphorylation of Ser118 and Ser167 in the AF1 domain of ERa drive estrogen-independent transcriptional activation and are associated with resistance to endocrine therapy. For example, HER2 overexpression results in ERa phosphorylation and resistance to tamoxifen treatment in vitro (Shou et al, 2004;Pancholi et al, 2008) and it is associated with resistance to endocrine therapy in vivo (Benz et al, 1992;Yamashita et al, 2008;Kok et al, 2009). In spite of this the molecular mechanisms governing resistance to endocrine therapy remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phosphorylation of Ser118 and Ser167 in the AF1 domain of ERa drive estrogen-independent transcriptional activation and are associated with resistance to endocrine therapy. For example, HER2 overexpression results in ERa phosphorylation and resistance to tamoxifen treatment in vitro (Shou et al, 2004;Pancholi et al, 2008) and it is associated with resistance to endocrine therapy in vivo (Benz et al, 1992;Yamashita et al, 2008;Kok et al, 2009). In spite of this the molecular mechanisms governing resistance to endocrine therapy remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we demonstrated that both exogenous (a relatively short period of treatment with recombinant IL6) and endogenous IL6 (as a result of transfection with plasmid encoding sense IL6) enhance expression of pERa-Ser118:total ERa and pERa-Ser167:total ERa in non-IL6-expressing A2780 cells, while deleting the endogenous IL6 expression in IL6-overexpressing CAOV-3 cells (due to transfection with plasmid encoding antisense IL6) reduces expression of pERa-Ser118:total ERa and pERa-Ser167:total ERa. Phosphorylation of ERa-Ser118 and ERa-Ser167 are two sites which have been shown to be involved in TAM resistance (Sarwar et al 2006, Yamashita et al 2008, Yamnik et al 2009, Guo et al 2010; we recently showed that there was a significantly increased resistance to TAM in A2780 cells pretreated with IL6 (A2780/preIL6) and ssIL6-transfected A2780 cells and a markedly increased responsiveness to TAM in asIL6-transfected CAOV-3 cells as compared with the corresponding control cells (Wang et al 2014). These findings indicate that IL6-induced TAM resistance may also be associated with increased expression of pERaSer118 and pERa-Ser167 in OVCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies in vivo and in vitro remain conflicting regarding whether pERa-Ser118 or pERa-Ser167 have an effect on TAM resistance (Mintz et al 2008, Yamashita et al 2008, Guo et al 2010, Motomura et al 2010, Chen et al 2013. Sarwar et al (2006) demonstrated that pERa-Ser118 was elevated in tumor biopsies taken from patients who had relapsed following TAM treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations